Photovoltaic cell and method for making the same
The integration of a modification layer formed from an amino acid solution addresses the conductivity and alignment issues in metal oxide hole transport layers within perovskite solar cells, resulting in improved energy conversion efficiency by enhancing the compatibility and optical properties of the layers.
Patent Information
- Application Number
- CN202411407121.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In existing perovskite solar cells, metal oxide-based hole transport layers exhibit low conductivity and poor light transmission due to defects and misalignment with the perovskite layer, leading to suboptimal energy conversion efficiency.
A method involving the use of a water-based amino acid solution to form a modification layer on the metal oxide hole transport layer, enhancing its conductivity and compatibility with the perovskite layer through hydrogen bonding, thereby improving the film's density and optical transparency.
This approach increases the hole transport layer's conductivity and light transmission, leading to improved solar cell efficiency by better matching the energy levels and reducing defects between the layers, thus enhancing the overall energy conversion efficiency.
Smart Images

Figure CN118922002B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaics, and in particular to a method for manufacturing a photovoltaic cell and a photovoltaic cell. Background Art
[0002] Perovskite cells have developed rapidly in recent years. Perovskite materials have the advantages of adjustable band gap and simple process. Their use as light energy absorbing materials in batteries has significantly improved battery performance.
[0003] In existing perovskite solar cells, the main materials of the hole transport layer include organic hole transport materials and metal oxides. Among them, organic hole transport materials include: PTAA (poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine]), PEDOT:PSS (poly 3,4-ethylenedioxythiophene / polystyrene sulfonate), etc.; metal oxides include: nickel oxide (NiO x ), copper oxide (CuO x ), molybdenum oxide (MoO x ) and so on. Compared with organic hole transport materials, metal oxides have the advantages of low cost, simple preparation process and high chemical stability. However, when preparing metal oxides, metal ion vacancies with high ionization energy are prone to occur, resulting in a low hole density and a low intrinsic conductivity of the hole transport layer; and the hole transport layer of the metal oxide material has too many surface defects on the side close to the perovskite layer, resulting in unsatisfactory transmittance of light penetrating the battery membrane structure. In addition, the energy level matching between the hole transport layer and the perovskite layer is often not ideal. For example, when nickel oxide is used as the material of the hole transport layer, the valence band bottom energy level of the hole transport layer is usually -5.09eV, while the valence band bottom energy level of the perovskite layer is -5.4eV. The energy level mismatch between the two will also affect the transmission and extraction rate of holes, thereby affecting the power generation efficiency of photovoltaic cells.
[0004] Therefore, when the hole transport layer uses metal oxide, how to improve the conductivity and transmittance of the hole transport layer to ensure the power generation efficiency of the photovoltaic cell has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention provides a method for manufacturing a photovoltaic cell and a photovoltaic cell, wherein the method for manufacturing a photovoltaic cell can ensure the conductivity and transmittance of the hole transport layer, improve the matching degree of the energy level between the hole transport layer and the perovskite layer, and improve the light conversion efficiency of the perovskite solar cell.
[0006] To achieve the above object, as one aspect of the present invention, a method for manufacturing a photovoltaic cell is provided, comprising:
[0007] A hole transport layer is formed on a conductive substrate, wherein the hole transport layer is a metal oxide;
[0008] Disposing a preset hydrophilic amino acid solution on the surface of the hole transport layer, and performing a first heating treatment so that the preset hydrophilic amino acid solution forms a modified layer above the hole transport layer;
[0009] forming a perovskite layer on the modified layer so that the amino acid molecules in the modified layer are connected to the perovskite layer through hydrogen bonds;
[0010] An electron transport layer and an electrode structure are fabricated above the perovskite layer.
[0011] Optionally, the solute of the predetermined hydrophilic amino acid solution includes at least one of asparagine, cysteine, glutamine, serine, tyrosine and threonine.
[0012] Optionally, the solute of the preset hydrophilic amino acid solution is at least one of the serine and the cysteine, and the solute concentration is 0.05 mg / ml to 0.2 mg / ml.
[0013] Optionally, the step of providing a preset hydrophilic amino acid solution on the surface of the hole transport layer and performing a first heating treatment comprises:
[0014] Immersing the hole transport layer in the preset hydrophilic amino acid solution and performing a first heating treatment at the same time, so that the modified layer is formed on the hole transport layer;
[0015] The temperature of the first heating treatment is 60° C. to 80° C., and the time of the first heating treatment is 40 min to 80 min.
[0016] Optionally, the first heating treatment includes: placing a first container carrying the preset hydrophilic amino acid solution into a second container carrying heated water, so that the outer wall of the first container is in contact with the heated water, and heating the second container.
[0017] Optionally, the method for manufacturing the photovoltaic cell further includes:
[0018] taking out the conductive substrate having the hole transport layer and the modified layer formed thereon from the preset hydrophilic amino acid solution;
[0019] The conductive substrate formed with the hole transport layer and the modified layer is subjected to a second heat treatment, wherein the temperature of the second heat treatment is 70° C. to 90° C., and the time of the second heat treatment is 2 min to 10 min.
[0020] Optionally, the second heating treatment of the conductive substrate having the hole transport layer and the modified layer formed thereon comprises:
[0021] The conductive substrate on which the hole transport layer and the modified layer are formed is placed on a hot stage and heated by the hot stage.
[0022] Optionally, the material of the hole transport layer includes nickel oxide.
[0023] Optionally, the step of fabricating a hole transport layer on a conductive substrate comprises:
[0024] heating the nickel oxide target material by electron beam to vaporize the material of the nickel oxide target material;
[0025] The vaporized nickel oxide particles condense on the surface of the conductive substrate to form the hole transport layer.
[0026] As a second aspect of the present invention, a photovoltaic cell is provided, which is manufactured by the photovoltaic cell manufacturing method described above, and comprises a conductive substrate, a hole transport layer, a modified layer, a perovskite layer, an electron transport layer and an electrode structure stacked in sequence, wherein the modified layer comprises a plurality of amino acid molecules, and the amino acid molecules are connected to the perovskite layer by hydrogen bonds.
[0027] Optionally, the conductive substrate includes a substrate and a first conductive layer stacked between the substrate and the hole transport layer, and the substrate is a silicon-based solar cell.
[0028] Optionally, the silicon-based solar cell is a heterojunction cell, comprising an N-type doped layer, a front intrinsic amorphous silicon layer, an N-type single crystal silicon wafer, a back intrinsic amorphous silicon layer, a P-type doped layer and a back transparent conductive layer stacked in sequence in a direction away from the perovskite layer.
[0029] In the photovoltaic cell and its manufacturing method provided by the present invention, the amino acid molecules in the modified layer have hydrophilic groups such as hydroxyl and carboxyl, so that the surface wettability of the hole transport layer can be improved, making it easier for the perovskite to spread on the surface of the hole transport layer with the modified layer, and fill the pores and defects in the hole transport layer film, thereby ensuring the overall density of the film, improving the flatness of the film surface to reduce light scattering, and increasing the transmittance of light when passing through the modified layer and the hole transport layer, so that the loss of light during propagation is reduced, thereby improving the utilization rate of light by the photovoltaic cell and the crystallization quality of the perovskite layer, thereby improving the power generation efficiency of the photovoltaic cell.
[0030] In addition, the carboxyl group in the amino acid molecule acts as an electron-withdrawing group. When in contact with the hole transport layer in a heated state, it can increase the content of cations in the hole transport layer, thereby improving the conductivity of the hole transport layer. At the same time, the modified layer can serve as an interface modification layer to improve the contact quality between the hole transport layer and the perovskite layer and reduce the interface defects at the junction of the two. The amino acid interacts with the defect sites on the surface of the hole transport layer, passivates the defect sites by chemical adsorption, and reduces the activity of the defect sites, thereby lowering the valence band bottom of the hole transport layer, ensuring the matching degree of energy levels between the hole transport layer and the perovskite layer, which is beneficial to the transmission and extraction of holes, and further improves the power generation efficiency of photovoltaic cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings:
[0032] Figure 1 is a schematic flow chart of a method for manufacturing a photovoltaic cell provided by an embodiment of the present invention;
[0033] Figures 2 to 5 It is a schematic diagram of the steps of the method for manufacturing a photovoltaic cell provided by an embodiment of the present invention;
[0034] Figure 6 It is a schematic diagram of the solute molecular structure of the preset hydrophilic amino acid solution in the method for manufacturing a photovoltaic cell provided by an embodiment of the present invention;
[0035] Figure 7 It is a schematic diagram comparing the test results of Test Example 1 and Comparative Example 1 in the method for manufacturing a photovoltaic cell provided in an embodiment of the present invention.
[0036] Description of Reference Numerals
[0037] 100: substrate; 200: first conductive layer; 300: hole transport layer; 400: modified layer; 500: perovskite layer; 600: electron transport layer; 610: hole blocking layer; 700: electrode structure. DETAILED DESCRIPTION
[0038] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments in the implementation manner are intended to be used to explain the present invention and should not be construed as limiting the present invention.
[0039] References to "one embodiment" or "example" or "example" in this specification mean that a particular feature, structure, or characteristic described in conjunction with the embodiment itself may be included in at least one embodiment disclosed herein. The appearance of the phrase "in one embodiment" in various places in the specification does not necessarily refer to the same embodiment.
[0040] In order to solve the above technical problems, as one aspect of the present invention, a method for manufacturing a photovoltaic cell is provided, such as Figure 1 As shown, the production method includes:
[0041] Step S10, forming a hole transport layer 300 (HTL) on a conductive substrate (including a substrate 100 and a first conductive layer 200 stacked in a thickness direction), wherein the hole transport layer 300 is a metal oxide;
[0042] Step S20: a preset hydrophilic amino acid solution is disposed on the surface of the hole transport layer 300, and a first heating treatment is performed to allow the preset hydrophilic amino acid solution to form a modified layer 400 on the hole transport layer 300. Figures 2 to 3 As shown;
[0043] Step S40: forming a perovskite layer 500 on the modified layer 400 so that the amino acid molecules in the modified layer 400 are connected to the perovskite layer 500 through hydrogen bonds, such as Figure 3 to Figure 4 As shown;
[0044] Step S50: fabricate an electron transport layer 600 (ETL) and an electrode structure 700 on the perovskite layer 500. Figures 4 to 5 shown.
[0045] In the method for manufacturing a photovoltaic cell provided by the present invention, a preset hydrophilic amino acid solution is firstly arranged on the surface of the hole transport layer 300 before manufacturing the perovskite layer 500, and the solution is heated so that the amphiphilic amino acid containing hydroxyl and carboxyl groups is adsorbed on the hole transport layer 300 to form a modified layer 400, and then the perovskite layer 500 is manufactured on the modified layer 400. The amino groups in the amino acid molecules can form hydrogen bonds with the halogen atoms and uncoordinated lead ions in the perovskite molecules, thereby ensuring the bonding strength between the perovskite layer 500 and the modified layer 400, and the amino acid molecules in the modified layer 400 have hydroxyl groups. , carboxyl and other hydrophilic groups, thereby improving the surface wettability of the hole transport layer 300, making it easier for the perovskite to spread on the surface of the hole transport layer 300 with the modified layer 400, and filling the pores and defects in the hole transport layer 300 film, ensuring the overall density of the film, improving the flatness of the film surface to reduce light scattering, and increasing the transmittance of light when passing through the modified layer 400 and the hole transport layer 300, so that the loss of light during propagation is reduced, thereby improving the utilization rate of light by the photovoltaic cell and the crystallization quality of the perovskite layer 500, thereby improving the power generation efficiency of the photovoltaic cell.
[0046] In addition, the carboxyl group in the amino acid molecule acts as an electron-withdrawing group. When in contact with the hole transport layer 300 under heating, it can increase the content of cations in the hole transport layer 300, thereby improving the conductivity of the hole transport layer 300. At the same time, the modified layer 400 can serve as an interface modification layer to improve the contact quality between the hole transport layer 300 and the perovskite layer 500, and reduce the interface defects at the junction of the two. The amino acid interacts with the defect sites on the surface of the hole transport layer 300, passivates the defect sites by chemical adsorption, and reduces the activity of the defect sites, thereby lowering the valence band bottom of the hole transport layer 300, ensuring the matching degree of energy levels between the hole transport layer 300 and the perovskite layer 500, which is beneficial to the transmission and extraction of holes, and further improves the power generation efficiency of photovoltaic cells.
[0047] According to tests, the valence band bottom energy level of the hole transport layer made of nickel oxide material without the modified layer 400 is -5.09 eV, while the valence band bottom energy level of the hole transport layer 300 made of nickel oxide material after the modified layer 400 is made can be reduced to -5.23 eV, which is closer to the valence band bottom energy level of the perovskite layer 500 -5.4 eV, and can significantly improve the energy level matching between the hole transport layer 300 and the perovskite layer 500.
[0048] It can be understood that in the present invention, the perovskite in the perovskite layer 500 refers to a compound having the same type of crystal structure (ABX3 structure) as CaTiO3.
[0049] As an optional embodiment of the present invention, Figure 6 As shown, the solvent of the preset hydrophilic amino acid solution is water, and the solute of the preset hydrophilic amino acid solution includes at least one of asparagine, cysteine, glutamine, serine, tyrosine and threonine.
[0050] In an embodiment of the present invention, the solute of the preset hydrophilic amino acid solution may include asparagine, cysteine, glutamine, serine, tyrosine, and threonine, all of which are hydrophilic amino acids, which can ensure the content of amino acid molecules in the preset hydrophilic amino acid solution, improve the growth efficiency of the modified layer 400, and thereby ensure the production efficiency of the photovoltaic cell.
[0051] As a preferred embodiment of the present invention, the solute of the hydrophilic amino acid solution is preset to be at least one of serine and cysteine.
[0052] Among the hydrophilic amino acids, serine and cysteine have particularly outstanding binding effects with perovskite. Specifically, although the above six amino acids can improve the wettability of nickel oxide, the side chains of threonine, tyrosine, glutamine, and asparagine are longer than those of serine and cysteine. Therefore, when these amino acids are chemically adsorbed on the surface of nickel oxide, steric hindrance reactions will occur in the molecules, resulting in low coverage on the surface of nickel oxide. The side chains of serine and cysteine are shorter and have hydroxyl and sulfhydryl groups, which can form coordination bonds with lead in perovskite (the amino group (-NH2) of serine can form coordination bonds with lead (Pb 2+ ) to form a coordination bond, and the thiol group (-SH) of cysteine can react with the lead (Pb 2+ ) form coordination bonds), and the two can also work synergistically to reduce the defects of perovskite films.
[0053] Therefore, the solute of the preset hydrophilic amino acid solution in the embodiment of the present invention is preferably at least one of serine and cysteine, which can further improve the overall density of the film, improve the flatness of the film surface and thus reduce light scattering, and increase the transmittance of light passing through the modified layer 400 and the hole transport layer 300, thereby reducing the loss of light during propagation, improving the utilization rate of light by the photovoltaic cell and the crystallization quality of the perovskite layer 500, thereby improving the power generation efficiency of the photovoltaic cell.
[0054] As a preferred embodiment of the present invention, when the solute of the preset hydrophilic amino acid solution is at least one of serine and cysteine, the solute concentration of the preset hydrophilic amino acid solution is 0.05 mg / ml to 0.2 mg / ml.
[0055] If the solute concentration of the hydrophilic amino acid solution is less than 0.05 mg / ml, the amino acid will combine slowly with the hydroxyl group on the surface of nickel oxide, which will lead to a long water bath heating time and low production experiment efficiency. If the solute concentration of the hydrophilic amino acid solution is greater than 0.2 mg / ml, after the self-assembled molecular layer is formed, there will be excess amino acids adsorbed on the surface of the hole transport layer, which need to be removed by additional cleaning, affecting the production efficiency.
[0056] As a preferred embodiment of the present invention, the material of the hole transport layer 300 includes nickel oxide (eg, nickel oxide (NiO)).
[0057] Hole transport materials mainly include nickel oxide (NiO x ), polystyrene sulfonate (PEDOT:PSS), copper oxide (CuO x ), molybdenum oxide (MoO x ) etc. Compared with organic hole transport materials and other metal oxides, inorganic hole material nickel oxide (NiOx ) has the advantages of low cost, simple preparation process and high chemical stability.
[0058] In the embodiment of the present invention, the material of the hole transport layer 300 includes nickel oxide, and the carboxyl group of the amino acid can react with the hydroxyl group on the surface of the nickel oxide to form a self-assembled monolayer of the amino acid, thereby ensuring the bonding strength between the modified layer 400 and the hole transport layer 300. At the same time, the electron-withdrawing group carboxyl group in the amino acid molecule can absorb electrons, thereby making the divalent nickel (Ni 2+ ) and trivalent nickel (Ni 3+ ) is increased, so that the number of holes in the hole transport layer 300 is greatly increased, thereby improving the conductive performance of the hole transport layer 300.
[0059] As an optional embodiment of the present invention, the thickness of the hole transport layer 300 is 20 nm to 50 nm.
[0060] As an optional embodiment of the present invention, the thickness of the hole transport layer 300 is 30 nm.
[0061] As an optional embodiment of the present invention, in step S20, the hole transport layer 300 or the entire substrate may be immersed in a preset hydrophilic amino acid solution to form a film on the surface of the hole transport layer 300. Specifically, step S20 may include:
[0062] The hole transport layer 300 is immersed in a predetermined hydrophilic amino acid solution and subjected to a first heat treatment, so that a modified layer 400 is formed on the hole transport layer 300 .
[0063] As an optional embodiment of the present invention, the temperature of the first heating treatment is 60° C. to 80° C., and the time of the first heating treatment is 40 min to 80 min.
[0064] As an optional embodiment of the present invention, the temperature of the first heating treatment is 70° C., and the time of the first heating treatment is 60 minutes.
[0065] To ensure uniform and sufficient heating in step S20, as a preferred embodiment of the present invention, step S20 can be implemented by water bath heating. Specifically, the first heating treatment in S20 specifically includes:
[0066] The first container carrying the preset hydrophilic amino acid solution is placed in the second container carrying heated water, so that the outer wall of the first container is in contact with the heated water, and the second container is heated.
[0067] The embodiment of the present invention heats the hydrophilic amino acid solution and the hole transport layer 300 by water bath heating. The temperature is transferred from the heated water in the second container to the first container and the preset hydrophilic amino acid solution therein. This can ensure the reaction temperature while avoiding local overheating of the hole transport layer 300 or the preset hydrophilic amino acid solution. It can effectively ensure the uniformity of the surface temperature distribution of the hole transport layer 300, thereby ensuring the uniformity of the film thickness of the modified layer 400.
[0068] In order to ensure the film strength of the modified layer 400, as a preferred embodiment of the present invention, the method further includes a step of heating and annealing to solidify the modified layer 400. Specifically, the method for manufacturing a photovoltaic cell further includes:
[0069] Step S31, taking out the conductive substrate formed with the hole transport layer 300 and the modified layer 400 from the preset hydrophilic amino acid solution;
[0070] Step S32 : performing a second heat treatment on the conductive substrate formed with the hole transport layer 300 and the modified layer 400 .
[0071] As an optional embodiment of the present invention, the temperature of the second heating treatment is 70° C. to 90° C., and the time of the second heating treatment is 2 min to 10 min.
[0072] As an optional embodiment of the present invention, the temperature of the second heating treatment is 80° C., and the time of the second heating treatment is 5 minutes.
[0073] As an optional embodiment of the present invention, the annealing step may be implemented by a hot stage. Specifically, step S32 may include:
[0074] The conductive substrate on which the hole transport layer 300 and the modified layer 400 are formed is placed on a hot stage and heated by the hot stage to cure the modified layer 400 .
[0075] As an optional embodiment of the present invention, the thickness of the perovskite layer 500 is 500 nm to 600 nm.
[0076] As an optional embodiment of the present invention, the thickness of the perovskite layer 500 is 550 nm.
[0077] As an optional embodiment of the present invention, the conductive substrate includes a substrate 100 and a first conductive layer 200 stacked in a thickness direction.
[0078] Optionally, the method for manufacturing a photovoltaic cell further comprises, before step S10, manufacturing a first conductive layer 200 on the substrate 100 to obtain a conductive substrate.
[0079] As an optional implementation of the present invention, the material of the substrate 100 includes glass.
[0080] As an optional implementation of the present invention, the material of the first conductive layer 200 includes indium tin oxide (ITO).
[0081] As an optional embodiment of the present invention, the method for manufacturing a photovoltaic cell further includes:
[0082] After the first conductive layer 200 is formed on the substrate 100 to obtain a conductive substrate, the conductive substrate is immersed in a preset cleaning solution for a first preset time.
[0083] As an optional embodiment of the present invention, the preset washing liquid includes detergent, deionized water, acetone and isopropyl alcohol.
[0084] As an optional implementation manner of the present invention, the first preset time is 15 minutes to 20 minutes.
[0085] As an optional embodiment of the present invention, the method further comprises, after the conductive substrate is cleaned, drying the surface of the first conductive layer 200 by using a preset inert gas.
[0086] As an optional embodiment of the present invention, the preset inert gas includes nitrogen (N2).
[0087] As an optional implementation of the present invention, the method further comprises placing the conductive substrate in a plasma cleaning machine for cleaning for a second preset time after the conductive substrate is cleaned.
[0088] As an optional implementation manner of the present invention, the second preset time is 15 minutes to 25 minutes.
[0089] As an optional implementation manner of the present invention, the second preset time is 20 minutes.
[0090] As an optional embodiment of the present invention, the hole transport layer 300 may be formed by an electron beam evaporation coating process. Specifically, step S10 may include:
[0091] Heating the nickel oxide target material by an electron beam to vaporize the material of the nickel oxide target material;
[0092] The vaporized nickel oxide particles condense on the surface of the conductive substrate to form the hole transport layer 300 .
[0093] Electron beam evaporation coating technology uses electron beams to accurately bombard nickel oxide targets, which can ensure the heating efficiency of nickel oxide targets, thereby accelerating the material evaporation rate and avoiding evaporation contamination of nickel oxide targets, ensuring the cleanliness of the chamber. In addition, this method can concentrate heat on the nickel oxide target, so that the conductive substrate does not have to withstand high temperatures, which can effectively reduce the possibility of thermal damage to the conductive substrate caused by high temperatures, thereby ensuring the stability of the film structure of the photovoltaic cell.
[0094] Further, step S10 can be implemented by an electron beam evaporation coating machine, and specifically includes:
[0095] The conductive substrate is placed in an electron beam evaporation coating machine, and when the vacuum degree in the electron beam evaporation coating machine reaches a first preset pressure, nickel oxide is evaporated to a preset thickness at a preset rate to obtain a hole transport layer 300 .
[0096] As an optional embodiment of the present invention, the first preset pressure is 8×10 -4 Pa to 9×10 -4 Pa.
[0097] As an optional embodiment of the present invention, the preset rate is 0.1Å / s to 0.2Å / s, and the preset thickness is 20 nm to 50 nm.
[0098] As an optional embodiment of the present invention, the preset rate is 0.15Å / s and the preset thickness is 30 nm.
[0099] As another optional embodiment of the present invention, the process of manufacturing the hole transport layer 300 on the first conductive layer 200 specifically includes:
[0100] The substrate 100 having the first conductive layer 200 is placed in an electron beam evaporation coating machine. When the vacuum degree in the electron beam evaporation coating machine reaches a first preset pressure, nickel oxide of a first preset thickness is sequentially evaporated at a first preset rate, nickel oxide of a second preset thickness is evaporated at a second preset rate, and nickel oxide of a third preset thickness is evaporated at a third preset rate to obtain a hole transport layer 300; wherein the first preset rate is less than the second preset rate, and the second preset rate is less than the third preset rate.
[0101] As an optional embodiment of the present invention, the first preset rate is 0.1 Å / s, the first preset thickness is 10 nm, the second preset rate is 0.2 Å / s, the second preset thickness is 15 nm, and the third preset rate is 0.3 Å / s, and the third preset thickness is 15 nm.
[0102] As an optional embodiment of the present invention, the step S20 of providing a preset hydrophilic amino acid solution on the surface of the hole transport layer 300 specifically includes:
[0103] The conductive substrate with the hole transport layer 300 is immersed in a container carrying a predetermined hydrophilic amino acid solution, and the container is placed in an oven.
[0104] As an optional embodiment of the present invention, the method for manufacturing a photovoltaic cell further includes:
[0105] Step S21 : After forming the modified layer 400 (step S20 ), removing the preset hydrophilic amino acid solution on the surface of the modified layer 400 .
[0106] As an optional embodiment of the present invention, removing the preset hydrophilic amino acid solution on the surface of the modified layer 400 in step S21 specifically includes:
[0107] The surface of the hole transport layer 300 is rinsed with deionized water, and the surface of the hole transport layer 300 is blown dry by a preset inert gas.
[0108] As an optional embodiment of the present invention, the material of the perovskite layer 500 includes methylamine iodide perovskite (MAPbI3), and the step S40 of making the perovskite layer 500 on the modified layer 400 specifically includes:
[0109] The substrate 100 having the first conductive layer 200 and the hole transport layer 300 is placed in a vacuum evaporator. When the vacuum degree in the vacuum evaporator reaches a second preset pressure, the temperature in the chamber is increased to evaporate lead iodide (PbI2) and methylamine iodine (MAI) at corresponding temperatures, respectively. The deposition is performed for a third preset time to obtain a thin film with a thickness of 400 nm. The substrate is heated at a preset temperature for a fourth preset time (RH=40%) to finally obtain a perovskite layer 500.
[0110] As an optional embodiment of the present invention, the second preset pressure is 8×10 -4 Pa.
[0111] As an optional implementation manner of the present invention, the third preset time is 80 min-120 min.
[0112] As an optional implementation manner of the present invention, the third preset time is 100 minutes.
[0113] As an optional implementation manner of the present invention, the preset temperature is 120° C.-170° C., and the fourth preset time is 20 min-40 min.
[0114] As an optional implementation manner of the present invention, the preset temperature is 150° C., and the fourth preset time is 30 minutes.
[0115] As an optional embodiment of the present invention, Figures 4 to 5 As shown, step S50 specifically includes:
[0116] Step S51, forming an electron transport layer 600 on the perovskite layer 500;
[0117] Step S52, forming a hole blocking layer 610 on the electron transport layer 600;
[0118] Step S53 , manufacturing the electrode structure 700 on the hole blocking layer 610 .
[0119] As an optional embodiment of the present invention, the material of the electron transport layer 600 includes C60.
[0120] As an optional embodiment of the present invention, the thickness of the electron transport layer 600 is 20 nm to 30 nm.
[0121] As an optional embodiment of the present invention, the thickness of the electron transport layer 600 is 25 nm.
[0122] As an optional embodiment of the present invention, in step S51, forming an electron transport layer 600 on the perovskite layer 500 includes:
[0123] The substrate 100 having the first conductive layer 200, the hole transport layer 300 and the perovskite layer 500 is placed in a vacuum coating machine. When the vacuum degree in the vacuum coating machine reaches a third preset pressure, a C60 film having a fourth preset thickness is evaporated on the perovskite layer 500 at a fourth preset rate to obtain an electron transport layer 600.
[0124] As an optional embodiment of the present invention, the third preset pressure is 8×10 -4 Pa.
[0125] As an optional embodiment of the present invention, the fourth preset rate is 0.1 Å / s, and the fourth preset thickness is 25 nm.
[0126] As an optional implementation of the present invention, the material of the hole blocking layer 610 includes BCP material.
[0127] As an optional embodiment of the present invention, the thickness of the hole blocking layer 610 is 5 nm to 10 nm.
[0128] As an optional embodiment of the present invention, the thickness of the hole blocking layer 610 is 8 nm.
[0129] As an optional embodiment of the present invention, in step S52, forming a hole blocking layer 610 on the electron transport layer 600 includes:
[0130] A substrate 100 having a first conductive layer 200, a hole transport layer 300, a perovskite layer 500 and an electron transport layer 600 is placed in a vacuum coating machine. When the vacuum degree in the vacuum coating machine reaches a fourth preset pressure, a BCP material of a fifth preset thickness is evaporated on the electron transport layer 600 at a fifth preset rate to obtain a hole blocking layer 610.
[0131] As an optional embodiment of the present invention, the fourth preset pressure is 8×10 -4 Pa.
[0132] As an optional embodiment of the present invention, the fifth preset rate is 0.1 Å / s, and the fifth preset thickness is 8 nm.
[0133] As an optional implementation of the present invention, the material of the electrode structure 700 includes silver.
[0134] As an optional embodiment of the present invention, the thickness of the electrode structure 700 is 110 nm to 130 nm.
[0135] As an optional implementation of the present invention, the thickness of the electrode structure 700 is 120 nm.
[0136] As an optional embodiment of the present invention, in step S53, the electrode structure 700 is fabricated on the hole blocking layer 610, including:
[0137] A substrate 100 having a first conductive layer 200, a hole transport layer 300, a perovskite layer 500, an electron transport layer 600 and a hole blocking layer 610 is placed in a metal vacuum coating machine. When the vacuum degree in the metal vacuum coating machine reaches a fifth preset pressure, a silver film having a sixth preset thickness is evaporated on the hole blocking layer 610 at a sixth preset rate to obtain the hole blocking layer 610.
[0138] As an optional embodiment of the present invention, the fifth preset pressure is 9×10 -4 Pa.
[0139] As an optional embodiment of the present invention, the sixth preset rate is 1 Å / s, and the sixth preset thickness is 120 nm.
[0140] To facilitate understanding by technicians, several embodiments of manufacturing photovoltaic cell structures using the photovoltaic cell manufacturing method provided by the present invention are provided below:
[0141] Embodiment 1:
[0142] ITO glass (i.e., a conductive substrate obtained by making a first conductive layer 200 of indium tin oxide on a glass substrate 100) is placed in containers containing detergent, deionized water, acetone, and isopropanol for ultrasonic cleaning for 15-20 minutes, and then dried with nitrogen for later use;
[0143] The cleaned ITO glass was placed in a plasma cleaning machine for 15 min, and then placed in an electron beam evaporation coating machine until the vacuum degree reached 9×10 -4 Pa, the coating was started, and a nickel oxide film with a thickness of 30 nm was evaporated at an evaporation rate of 0.15 Å / s to obtain a precursor substrate;
[0144] The precursor substrate is placed in a first container containing a preset hydrophilic amino acid solution, wherein the solutes of the preset hydrophilic amino acid solution include asparagine, serine and threonine, and the first container is placed in a second container containing water so that the outer wall of the first container is in contact with the water. The second container is placed in an oven and heated in a water bath at 70° C. for 1 hour to obtain a modified layer, and then the excess amino acids on the surface are washed with deionized water, and blown dry with a nitrogen gun, and then annealed on a hot stage at 80° C. for 5 minutes to solidify the modified layer;
[0145] MAPbI3 perovskite film was prepared by co-evaporation. When the vacuum degree of the chamber reached 8×10 -4 Pa, the temperature was adjusted, and the PbI2 source and MAI source were evaporated at 300 °C and 125 °C, respectively. The entire deposition time was 100 min to obtain a film with a thickness of 400 nm. Finally, it was annealed on a hot stage at 150 °C for 30 min (RH = 40%) to finally obtain a perovskite layer with a thickness of 550 nm.
[0146] The vacuum degree in the chamber reaches 8×10 -4 When the temperature is 2400 Pa, C60 with a film thickness of 25 nm is firstly evaporated on the perovskite film at a rate of 0.1 Å / s to obtain an electron transport layer 600, and then BCP material with a film thickness of 8 nm is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer 610;
[0147] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm was evaporated at an evaporation rate of 1 Å / s to obtain an electrode structure of 700.
[0148] Embodiment 2:
[0149] Place the ITO glass in detergent, deionized water, acetone, and isopropanol for ultrasonic treatment for 15-20 minutes, then dry it with nitrogen gas for later use;
[0150] The cleaned ITO glass was placed in a plasma cleaning machine for 20 min, and then placed in an electron beam evaporation coating machine until the vacuum degree reached 8×10 -4 Pa, adjusting the rate to start film deposition, evaporating a nickel oxide film with a thickness of 10 nm at an evaporation rate of 0.1 Å / s, evaporating a nickel oxide film with a thickness of 15 nm at an evaporation rate of 0.2 Å / s, and evaporating a nickel oxide film with a thickness of 15 nm at an evaporation rate of 0.3 Å / s, to obtain a nickel oxide film with a total thickness of 40 nm, to obtain a precursor substrate;
[0151] The precursor substrate is placed in a first container containing a preset hydrophilic amino acid solution, wherein the solutes of the preset hydrophilic amino acid solution include asparagine, cysteine and threonine, and the first container is placed in a second container containing water so that the outer wall of the first container is in contact with the water. The second container is placed in an oven and immersed in a water bath at 80°C for 40 minutes to obtain a modified layer, and then the excess amino acids on the surface are washed with deionized water and blown dry with a nitrogen gun, and then annealed on a hot stage at 70°C for 10 minutes to solidify the modified layer;
[0152] FACsPbI3 perovskite thin films were prepared by co-evaporation. When the vacuum degree of the chamber reached 8×10 -4 Pa, the temperature was adjusted, and PbI2, CsI source and FAI were evaporated at 300 °C, 350 °C and 150 °C, respectively. The temperature was adjusted to control the evaporation rate, and PbI2, CsI and FAI were evaporated at a rate of 1 Å / s, 0.25 Å / s and 1.51 Å / s, respectively. After 80 min of deposition, a film with a thickness of 420 nm was obtained. Finally, it was annealed on a hot stage at 170 °C in a nitrogen environment for 20 min (RH=40%), and finally a perovskite layer with a thickness of 500 nm was obtained;
[0153] The vacuum degree in the chamber reaches 8×10 -4 When the temperature is 2400 Pa, C60 with a film thickness of 25 nm is firstly evaporated on the perovskite film at a rate of 0.1 Å / s to obtain an electron transport layer 600, and then BCP material with a film thickness of 8 nm is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer 610;
[0154] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm was evaporated at an evaporation rate of 1 Å / s to obtain an electrode structure of 700.
[0155] Embodiment 3:
[0156] Place the ITO glass in detergent, deionized water, acetone, and isopropanol for ultrasonic treatment for 15-20 minutes, then dry it with nitrogen gas for later use;
[0157] The cleaned ITO glass was placed in a plasma cleaning machine for 25 min and then placed in an electron beam evaporation coating machine until the vacuum degree reached 9×10 -4 Pa, a nickel oxide film with a thickness of 20 nm was evaporated at an evaporation rate of 0.1 Å / s to obtain a precursor substrate;
[0158] The precursor substrate is placed in a first container containing a preset hydrophilic amino acid solution, wherein the solutes of the preset hydrophilic amino acid solution include cysteine, glutamine, tyrosine and threonine, and the first container is placed in a second container containing water so that the outer wall of the first container is in contact with the water. The second container is placed in an oven and immersed in a water bath at 60°C for 80 minutes to obtain a modified layer, and then the excess amino acids on the surface are washed with deionized water and blown dry with a nitrogen gun, and then annealed on a hot stage at 90°C for 2 minutes to solidify the modified layer;
[0159] MAPbI3 perovskite film was prepared by co-evaporation. When the vacuum degree of the chamber reached 8×10 -4 Pa, the temperature was adjusted, and the PbI2 source and MAI source were evaporated at 300 °C and 125 °C, respectively. The entire deposition time was 100 min to obtain a film with a thickness of 400 nm. Finally, it was annealed on a hot stage at 150 °C for 40 min (RH = 40%) to obtain a perovskite layer with a thickness of 600 nm.
[0160] The vacuum degree in the chamber reaches 8×10 -4 When the temperature is 2400 Pa, C60 with a film thickness of 25 nm is firstly evaporated on the perovskite film at a rate of 0.1 Å / s to obtain an electron transport layer 600, and then BCP material with a film thickness of 8 nm is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer 610;
[0161] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm was evaporated at an evaporation rate of 1 Å / s to obtain an electrode structure of 700.
[0162] Embodiment 4:
[0163] Place the ITO glass in detergent, deionized water, acetone, and isopropanol for ultrasonic treatment for 15-20 minutes, then dry it with nitrogen gas for later use;
[0164] The cleaned ITO glass was placed in a plasma cleaning machine for 25 min and then placed in an electron beam evaporation coating machine until the vacuum degree reached 8×10 -4 Pa, a nickel oxide film with a thickness of 50 nm was evaporated at an evaporation rate of 0.2 Å / s to obtain a precursor substrate;
[0165] The precursor substrate is placed in a first container containing a preset hydrophilic amino acid solution, wherein the solutes of the preset hydrophilic amino acid solution include cysteine, glutamine and serine, and the first container is placed in a second container containing water so that the outer wall of the first container is in contact with the water. The second container is placed in an oven and immersed in a water bath at 60°C for 1 hour to obtain a modified layer, and then the excess amino acids on the surface are washed with deionized water and blown dry with a nitrogen gun, and then annealed on a hot stage at 80°C for 5 minutes to solidify the modified layer;
[0166] FACsPbI3 perovskite thin films were prepared by co-evaporation. When the vacuum degree of the chamber reached 8×10 -4 Pa, the temperature was adjusted, and PbI2, CsI source and FAI were evaporated at 300 °C, 350 °C and 150 °C, respectively. The temperature was adjusted to control the evaporation rate, and PbI2, CsI and FAI were evaporated at a rate of 1 Å / s, 0.25 Å / s and 1.51 Å / s, respectively. After 80 min of deposition, a film with a thickness of 420 nm was obtained. Finally, it was annealed on a hot stage at 170 °C in a nitrogen environment for 20 min (RH=40%), and finally a perovskite layer with a thickness of 500 nm was obtained;
[0167] The vacuum degree in the chamber reaches 8×10 -4 When the temperature is 2400 Pa, C60 with a film thickness of 25 nm is firstly evaporated on the perovskite film at a rate of 0.1 Å / s to obtain an electron transport layer 600, and then BCP material with a film thickness of 8 nm is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer 610;
[0168] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm was evaporated at an evaporation rate of 1 Å / s to obtain an electrode structure of 700.
[0169] In order to demonstrate the excellent performance of the cell structure produced by the photovoltaic cell manufacturing method provided by the present invention, the following provides a test example of using the photovoltaic cell manufacturing method provided by the present invention to manufacture a film layer structure and perform a test, as well as a comparative example of using an existing manufacturing method to manufacture a film layer structure and perform the same test, so as to test the effect of the photovoltaic cell manufacturing method provided by the present invention on improving the transmittance and conductivity of the film layer by comparison.
[0170] Test Example 1:
[0171] Place the ITO glass in containers containing detergent, deionized water, acetone, and isopropanol for ultrasonic cleaning for 15-20 minutes, and blow dry with nitrogen gas for later use;
[0172] The cleaned ITO glass was placed in a plasma cleaning machine for 15 min, and then placed in an electron beam evaporation coating machine until the vacuum degree reached 9×10 -4 Pa, the coating was started, and a nickel oxide film with a thickness of 30 nm was evaporated at an evaporation rate of 0.15 Å / s to obtain a precursor substrate;
[0173] The precursor substrate is placed in a first container containing a preset hydrophilic amino acid solution, wherein the solutes of the preset hydrophilic amino acid solution include asparagine, cysteine, glutamine, serine, tyrosine and threonine, the first container is placed in a second container containing water, so that the outer wall of the first container is in contact with the water, the second container is placed in an oven, and immersed in a water bath at 70° C. for 1 hour to obtain a modified layer, and then the excess amino acids on the surface are washed with deionized water, and blown dry with a nitrogen gun, and then annealed on a hot stage at 80° C. for 5 minutes to solidify the modified layer;
[0174] The transmittance of the nickel oxide film containing the modified layer at each wavelength in the visible light range was tested by an ultraviolet-visible spectrophotometer.
[0175] Comparative Example 1:
[0176] Place the ITO glass in detergent, deionized water, acetone, and isopropanol for ultrasonic treatment for 15-20 minutes, then dry it with nitrogen gas for later use;
[0177] A nickel oxide solution with a concentration of 15 mg / mL (solvent: deionized water) was prepared, 150 μL was drawn by a pipette, spin-coated at 2000 rpm for 30 s, and annealed on a hot plate at 150°C for 10 min to form a nickel oxide film;
[0178] The transmittance of the nickel oxide film prepared by the spin coating method to light of various wavelengths in the visible light range was tested by an ultraviolet-visible spectrophotometer.
[0179] Test Example 2:
[0180] Place the ITO glass in containers containing detergent, deionized water, acetone, and isopropanol for ultrasonic cleaning for 15-20 minutes, and blow dry with nitrogen gas for later use;
[0181] The cleaned ITO glass was placed in a plasma cleaning machine for 15 min, and then placed in an electron beam evaporation coating machine until the vacuum degree reached 9×10 -4 Pa, the coating was started, and a nickel oxide film with a thickness of 30 nm was evaporated at an evaporation rate of 0.15 Å / s to obtain a precursor substrate;
[0182] Put the precursor substrate into a first container containing a preset hydrophilic amino acid solution, wherein the solute of the preset hydrophilic amino acid solution includes serine and cysteine, and the solute concentration of the preset hydrophilic amino acid solution is 0.1 mg / ml, wherein the molar ratio of serine to cysteine is 1:1, put the first container into a second container containing water, so that the outer wall of the first container is in contact with the water, put the second container in an oven, and soak it in a water bath at 70° C. for 1 hour to obtain a modified layer, then take out and rinse the excess amino acids on the surface with deionized water, blow dry with a nitrogen gun, and then anneal on a hot stage at 80° C. for 5 minutes to solidify the modified layer;
[0183] The MAPbI3 perovskite film was prepared by a one-step spin coating method. First, the perovskite precursor solution was prepared, and MAI and PbI2 were dissolved in a mixed solution of DMF:DMSO=4:1 at a molar ratio of 1:1. After sufficient dissolution, 120 μL of the perovskite precursor solution was taken and spin-coated at a speed of 1000 rpm for 10 seconds and then at a speed of 5000 rpm for 30 seconds. In the last 15 seconds, 120 μL of anti-solvent CB was added dropwise, and then annealed on a hot plate at 100°C for 10 minutes to obtain the perovskite layer;
[0184] The vacuum degree in the chamber reaches 8×10 -4 When the perovskite film is at 25 nm thick, C60 is firstly evaporated at a rate of 0.1 Å / s to obtain an electron transport layer, and then BCP material is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer.
[0185] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm (i.e., electrode structure) was evaporated at an evaporation rate of 1 Å / s to obtain a photovoltaic cell structure;
[0186] The obtained photovoltaic cell structure was subjected to IV test to detect the open circuit voltage (Voc), short circuit current density (J SC ), fill factor (FF) and photoelectric conversion efficiency (PCE).
[0187] Test Example 3:
[0188] Place the ITO glass in containers containing detergent, deionized water, acetone, and isopropanol for ultrasonic cleaning for 15-20 minutes, and blow dry with nitrogen gas for later use;
[0189] The cleaned ITO glass was placed in a plasma cleaning machine for 15 min, and then placed in an electron beam evaporation coating machine until the vacuum degree reached 9×10 -4 Pa, the coating was started, and a nickel oxide film with a thickness of 30 nm was evaporated at an evaporation rate of 0.15 Å / s to obtain a precursor substrate;
[0190] Putting a precursor substrate into a first container containing a preset hydrophilic amino acid solution, wherein the solute of the preset hydrophilic amino acid solution includes asparagine, cysteine, glutamine, serine, tyrosine and threonine, the solute concentration of the preset hydrophilic amino acid solution is 0.1 mg / ml, and the molar ratio of the six amino acids is 1:1:1:1:1:1:1, placing the first container into a second container containing water so that the outer wall of the first container is in contact with the water, placing the second container in an oven, and soaking it in a water bath at 70° C. for 1 hour to obtain a modified layer, then taking out and rinsing excess amino acids on the surface with deionized water, and drying it with a nitrogen gun, and then annealing on a hot stage at 80° C. for 5 minutes to solidify the modified layer;
[0191] The MAPbI3 perovskite film was prepared by a one-step spin coating method. First, the perovskite precursor solution was prepared, and MAI and PbI2 were dissolved in a mixed solution of DMF:DMSO=4:1 at a molar ratio of 1:1. After sufficient dissolution, 120 μL of the perovskite precursor solution was taken and spin-coated at a speed of 1000 rpm for 10 seconds and then at a speed of 5000 rpm for 30 seconds. In the last 15 seconds, 120 μL of anti-solvent CB was added dropwise, and then annealed on a hot plate at 100°C for 10 minutes to obtain the perovskite layer;
[0192] The vacuum degree in the chamber reaches 8×10 -4 When the perovskite film is at 25 nm thick, C60 is firstly evaporated at a rate of 0.1 Å / s to obtain an electron transport layer, and then BCP material is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer.
[0193] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm (i.e., electrode structure) was evaporated at an evaporation rate of 1 Å / s to obtain a photovoltaic cell structure;
[0194] The obtained photovoltaic cell structure was subjected to an IV test to detect the open circuit voltage (Voc), short circuit current density (JSC), fill factor (FF) and photoelectric conversion efficiency (PCE) of the photovoltaic cell structure.
[0195] Comparative Example 2:
[0196] Place the ITO glass in detergent, deionized water, acetone, and isopropanol for ultrasonic treatment for 15-20 minutes, then dry it with nitrogen gas for later use;
[0197] The cleaned ITO glass was placed in a plasma cleaning machine for 15 min, and then placed in an electron beam evaporation coating machine until the vacuum degree reached 9×10 -4Pa, the coating was started, and a nickel oxide film with a thickness of 30 nm was evaporated at an evaporation rate of 0.15 Å / s to obtain a precursor substrate;
[0198] The MAPbI3 perovskite film was prepared by a one-step spin coating method. First, the perovskite precursor solution was prepared, and MAI and PbI2 were dissolved in a mixed solution of DMF:DMSO=4:1 at a molar ratio of 1:1. After sufficient dissolution, 120 μL of the perovskite precursor solution was taken and spin-coated at a speed of 1000 rpm for 10 seconds and then at a speed of 5000 rpm for 30 seconds. In the last 15 seconds, 120 μL of anti-solvent CB was added dropwise, and then annealed on a hot plate at 100°C for 10 minutes to obtain the perovskite layer;
[0199] The vacuum degree in the chamber reaches 8×10 -4 When the perovskite film is at 25 nm thick, C60 is firstly evaporated at a rate of 0.1 Å / s to obtain an electron transport layer, and then BCP material is evaporated at an evaporation rate of 0.1 Å / s to obtain a hole blocking layer.
[0200] The vacuum degree in the chamber reaches 9×10 -4 Pa, a silver electrode with a thickness of 120 nm (i.e., electrode structure) was evaporated at an evaporation rate of 1 Å / s to obtain a photovoltaic cell structure;
[0201] The obtained photovoltaic cell structure was subjected to IV test to detect the open circuit voltage (Voc), short circuit current density (J SC ), fill factor (FF) and photoelectric conversion efficiency (PCE).
[0202] like Figure 7 Shown are the transmittance curves of the thin films obtained in Test Example 1 and Comparative Example 1 for light of various wavelengths. From the test results, it can be seen that the transmittance of the film structure manufactured by the photovoltaic cell manufacturing method provided by the present invention for light of various wavelengths is improved.
[0203] As shown in Table 1-1, the results of IV testing of Test Example 2 and Comparative Example 2 are shown respectively. From the test results, it can be seen that the photovoltaic cell structure manufactured by the method for manufacturing photovoltaic cells provided by the present invention has an increase in open circuit voltage, an increase in short circuit current density, an increase in fill factor, and an increase in photoelectric conversion efficiency. The method for manufacturing photovoltaic cells provided by the present invention can effectively improve the cell efficiency and ensure the photovoltaic power generation efficiency. Moreover, when serine and cysteine are used as the solutes of the preset hydrophilic amino acid solution (i.e., the case of Test Example 2), the improvement effect on the open circuit voltage, short circuit current density, fill factor, and photoelectric conversion efficiency of the photovoltaic cell structure is particularly prominent.
[0204] Table 1-1 Results of IV testing of Test Example 2, Test Example 3 and Comparative Example 2
[0205]
[0206] As a second aspect of the present invention, a photovoltaic cell is provided. The photovoltaic cell is manufactured by the above-mentioned method for manufacturing a photovoltaic cell, such as Figure 5 As shown, the photovoltaic cell includes a conductive substrate, a hole transport layer 300, a modified layer 400, a perovskite layer 500, an electron transport layer 600 and an electrode structure 700 which are stacked in sequence, wherein the modified layer 400 includes a plurality of amino acid molecules, and the amino acid molecules are connected to the perovskite layer through hydrogen bonds.
[0207] In the photovoltaic cell provided by the present invention, a modified layer 400 is formed between the perovskite layer 500 and the hole transport layer 300. The amino acid molecules in the modified layer 400 have hydrophilic groups such as hydroxyl groups and carboxyl groups, thereby improving the surface wettability of the hole transport layer 300, making it easier for the perovskite to spread on the surface of the hole transport layer 300 with the modified layer 400, and fill the pores and defects in the hole transport layer 300 film, thereby ensuring the overall density of the film, improving the flatness of the film surface, thereby reducing light scattering, and improving the transmittance of light when passing through the modified layer 400 and the hole transport layer 300, so that the loss of light during propagation is reduced, thereby improving the utilization rate of light by the photovoltaic cell and the crystallization quality of the perovskite layer 500, thereby improving the power generation efficiency of the photovoltaic cell.
[0208] In addition, the carboxyl group in the amino acid molecule acts as an electron-withdrawing group. When in contact with the hole transport layer 300 under heating, it can increase the content of cations in the hole transport layer 300, thereby improving the conductivity of the hole transport layer 300. At the same time, the modified layer 400 can serve as an interface modification layer to improve the contact quality between the hole transport layer 300 and the perovskite layer 500, and reduce the interface defects at the junction of the two. The amino acid interacts with the defect sites on the surface of the hole transport layer 300, passivates the defect sites by chemical adsorption, and reduces the activity of the defect sites, thereby lowering the valence band bottom of the hole transport layer 300, ensuring the matching degree of energy levels between the hole transport layer 300 and the perovskite layer 500, which is beneficial to the transmission and extraction of holes, and further improves the power generation efficiency of photovoltaic cells.
[0209] As an optional embodiment of the present invention, Figure 5 As shown, the photovoltaic cell further includes a hole blocking layer 610 stacked between the electron transport layer 600 and the electrode structure 700 .
[0210] As an optional embodiment of the present invention, the photovoltaic cell may be a perovskite tandem cell, specifically, Figure 5As shown, the conductive substrate includes a substrate 100 and a first conductive layer 200 stacked between the substrate 100 and the hole transport layer, and the substrate 100 is a silicon-based solar cell.
[0211] As an optional embodiment of the present invention, the silicon-based solar cell can be a heterojunction (HeteroJunction with intrinsic Thin-layer, HJT) cell, including an N-type doped layer, a front intrinsic amorphous silicon layer, an N-type single crystal silicon wafer, a back intrinsic amorphous silicon layer, a P-type doped layer and a back transparent conductive layer stacked in sequence along a direction away from the perovskite layer.
[0212] Optionally, the N-type doped layer may be an N-type amorphous silicon layer or an N-type microcrystalline silicon layer, and the P-type doped layer may be a P-type amorphous silicon layer or a P-type microcrystalline silicon layer.
[0213] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A method for manufacturing a photovoltaic cell, characterized in that: include: A hole transport layer is formed on a conductive substrate, wherein the hole transport layer is a metal oxide; A preset hydrophilic amino acid solution is disposed on the surface of the hole transport layer, and a first heating treatment is performed in a water bath so that the preset hydrophilic amino acid solution forms a modified layer above the hole transport layer; wherein the temperature of the first heating treatment is 60° C. to 80° C.; forming a perovskite layer on the modified layer so that the amino acid molecules in the modified layer are connected to the perovskite layer through hydrogen bonds; An electron transport layer and an electrode structure are fabricated above the perovskite layer, wherein: Before forming the perovskite layer on the modified layer, the manufacturing method further comprises: The conductive substrate having the hole transport layer and the modified layer formed thereon is subjected to a second heat treatment to obtain a cured modified layer.
2. The method for manufacturing a photovoltaic cell according to claim 1, characterized in that: The solute of the predetermined hydrophilic amino acid solution includes at least one of asparagine, cysteine, glutamine, serine, tyrosine and threonine.
3. The method for manufacturing a photovoltaic cell according to claim 2, characterized in that: The solute of the preset hydrophilic amino acid solution is at least one of the serine and the cysteine, and the solute concentration is between 0.05 mg / ml and 0.2 mg / ml.
4. The method for manufacturing a photovoltaic cell according to claim 1, characterized in that: A preset hydrophilic amino acid solution is disposed on the surface of the hole transport layer, and a first heating treatment is performed in a water bath, comprising: Immersing the hole transport layer in the preset hydrophilic amino acid solution and performing a first heating treatment in a water bath to form the modified layer on the hole transport layer; The first heating treatment lasts for 40 to 80 minutes.
5. The method for manufacturing a photovoltaic cell according to claim 4, characterized in that: The first heating treatment is performed by water bath, comprising: The first container carrying the preset hydrophilic amino acid solution is placed in the second container carrying heated water, so that the outer wall of the first container is in contact with the heated water, and the second container is heated.
6. The method for manufacturing a photovoltaic cell according to claim 1, characterized in that: The step of performing a second heating treatment on the conductive substrate having the hole transport layer and the modified layer formed thereon to obtain a cured modified layer comprises: taking out the conductive substrate having the hole transport layer and the modified layer formed thereon from the preset hydrophilic amino acid solution; The conductive substrate formed with the hole transport layer and the modified layer is subjected to a second heat treatment, wherein the temperature of the second heat treatment is 70° C. to 90° C., and the time of the second heat treatment is 2 min to 10 min.
7. The method for manufacturing a photovoltaic cell according to claim 6, characterized in that: The second heating treatment of the conductive substrate having the hole transport layer and the modified layer formed thereon comprises: The conductive substrate on which the hole transport layer and the modified layer are formed is placed on a hot stage and heated by the hot stage.
8. The method for manufacturing a photovoltaic cell according to any one of claims 1 to 4, characterized in that: The material of the hole transport layer includes nickel oxide; the method of making the hole transport layer on the conductive substrate includes: heating the nickel oxide target material by electron beam to vaporize the material of the nickel oxide target material; The vaporized nickel oxide particles condense on the surface of the conductive substrate to form the hole transport layer.
9. A photovoltaic cell, characterized in that: The photovoltaic cell is manufactured by the photovoltaic cell manufacturing method described in any one of claims 1 to 8, and the photovoltaic cell includes a conductive substrate, a hole transport layer, a modified layer, a perovskite layer, an electron transport layer and an electrode structure stacked in sequence, wherein the modified layer includes a plurality of amino acid molecules, and the amino acid molecules are connected to the perovskite layer through hydrogen bonds.
10. The photovoltaic cell according to claim 9, characterized in that: The conductive substrate includes a substrate and a first conductive layer stacked between the substrate and the hole transport layer. The substrate is a heterojunction battery, including an N-type doped layer, a front intrinsic amorphous silicon layer, an N-type single crystal silicon wafer, a back intrinsic amorphous silicon layer, a P-type doped layer and a back transparent conductive layer stacked in sequence along a direction away from the perovskite layer.
Citation Information
Patent Citations
Efficient nickel oxide-based perovskite solar cell based on amino acid and preparation method of efficient nickel oxide-based perovskite solar cell
CN116916667A